Testing happiness hypothesis among the elderly (2008)
We use a rich data set that allows us to test different happiness hypotheses employing four methodological approaches. We find that older people in Uruguay have a tendency to report themselves happy when they are married, when they have higher standards of health and when they earn higher levels of income or they consider that their income is suitable for their standard of living. On the contrary, they report lower levels of happiness when they live alone and when their nutrition is insufficient. We also find that education has no clear impact on happiness. We think that our study is a contribution to the study of those factors that can explain happiness among the elderly in Latin American countries. Future work will focus on enhanced empirical analysis and in extending our study to other countries.